The Impact of Microfinance Institutions on the Growth of Umkm: a Case Study of Baitul Maal Wa Tamwil (BMT) at Al-Amin Mosque, Deli Serdang - Hani, Fildzah; Syahputri, Salsabila; Ritonga, Dendi Dwi Putra; Hayati, Fitri (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
This study aims to analyze the impact of Baitul Maal wa Tamwil (BMT) at Al-Amin Mosque, Deli Serdang, on the growth of Micro, Small, and Medium Enterprises (MSMEs). Using a mixed-method approach through quantitative surveys and qualitative interviews, this study examines changes in indicators of turnover, business assets, workforce, and profitability of MSMEs before and after receiving financing from BMT. The results of the study indicate that BMT financing services have a positive impact on MSME growth. Average turnover increased by 60%, business assets increased, and 40% of respondents were able to employ additional workers. In addition, business profitability also increased significantly. However, this study also found several obstacles, such as low financial management capabilities and limited market access. This indicates the need to strengthen technology-based service innovation and coaching programs to support the sustainability of MSMEs. This study concludes that BMTs play a strategic role in empowering the local economy through sharia-based microfinance services. The results of this study provide recommendations for the development of similar MFIs to support MSME growth more effectively and inclusively.